Cost Behavior: An Empirical Analysis of Determinants and Consequences of Asymmetries - Kira Hoffmann (Copenhagen Business School (CBS), 2017)
The objective of this dissertation is to investigate determinants and consequences of asymmetric cost behavior. Asymmetric cost behavior arises if the change in costs is different for increases in activity compared to equivalent decreases in activity. In this case, costs are termed “sticky” if the change is less when activity falls than when activity rises, whereas costs are termed “anti-sticky” if the change is more when activity falls than when activity rises. Understanding such cost behavior is especially relevant for decision-makers and financial analysts that rely on accurate cost information to facilitate resource planning and earnings forecasting. As such, this dissertation relates to the topic of firm profitability and the interpretation of cost variability. The dissertation consists of three parts that are written in the form of separate academic papers. The following section briefly summarizes the main research question, methodological design, data, findings and practical implications of each paper.
hdl:10398/9449
Keywords: 650